Which Frequency of Ankle Pump Exercise Should Be Chosen for the Prophylaxis of Deep Vein Thrombosis? - Haiyan Li MD, RN; Wei Zhang PhD; Qingsheng Lu PhD; Jinping Wang RN; Yanru Zhi RN; Lingjuan Zhang PhD, RN; Lanshu Zhou PhD (SAGE Publishing, 2022)
Introduction Ankle pump exercise (APE) is an effective method to prevent deep vein thrombosis (DVT) in the lower extremities. However, traditional APE at a frequency of 3 times/min applied in the clinic lacked high compliance, and individuals were found to prefer an APE of 30 times/min. This study aimed to compare the effects of APEs with the above two different frequencies on the venous hemodynamics and fatigue of lower extremities. Methods The study applied a randomized cross-over design, and 307 healthy adults were randomly assigned into two groups, whose left feet performed 5 minutes of traditional APE (3 times/min, after 10 minutes of rest) and 5 minutes of selected APE (30 times/min, after 10 minutes of rest) in different orders. The diameters and blood flow velocities of the external iliac vein, femoral vein, and popliteal vein of the left extremities were recorded with the color doppler ultrasound when participants were at rest and after 5 minutes of traditional or selected APE. The fatigue of lower extremities was assessed with the Rating of Perceived Exertion (RPE) after the participants performed 5 minutes of different APEs. Results After both traditional APE and selected APE, the diameters and blood flow (peak systolic) velocities of the external iliac vein, femoral vein, and popliteal vein increased significantly in the participants (P<.01), and the effects of the two APEs on venous hemodynamics of the lower extremities had no significant difference (P>.05). However, participants reported that traditional APE caused higher fatigue, and 252 (82.1%) participants preferred APE at 30 times/min. Conclusion Both traditional and selected APE could increase venous blood flow in the lower extremity. Despite the equivalent effects, the selected APE of 30 times/min may cause less fatigue than the traditional one of 3 times/min.